Penerapan Media Video Pembelajaran dalam Meningkatkan Minat Belajar PPKn Siswa Kelas III SDN 008 Sungai Kunjang - Puja Saraswati, Raditya; Iksam; Taufik Hidayat (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, 2025)
The lack of learning interest of SDN 008 Sungai Kunjang grade III students, especially in the subject of PPKn, prompted this study to examine the effect of implementing learning video media on increasing students' learning interest. This study used a descriptive qualitative approach with data collection methods through questionnaires, interviews, observations, and documentation. Data analysis techniques used included data reduction, data display, and conclusion. The study results showed that using creative and interactive learning video media can increase students' interest, motivation, and participation in PPKn learning. Learning videos are considered effective in facilitating students' understanding of the material, as well as increasing their enthusiasm and involvement in the learning process. In addition, the findings of this study indicate that learning videos have great potential to be an alternative media that is more interesting and motivating for students, especially in the context of PPKn learning. Based on these findings, it is recommended that teachers use relevant learning videos and the needs of the material to improve the quality of the learning process in the classroom.